Pemberdayaan Kader Kesehatan Dengan Diabetes Self Management Education (DSME) untuk meningkatkan Self Manajemen Pasien Diabetes - M. Syikir; Dian Ayu Lestari; Suherman Suherman; Nurhidayah Syerman; Kiki Sanrila (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Background: Diabetes mellitus (DM) is included in a group of metabolic disorders with the characteristics of hyperglycemia which occurs due to insulin abnormalities caused by impaired insulin secretion. Diabetes Self Management Education (DSME) is an effort that can be made to provide ongoing education for DM clients. The DSME strategy was developed in health services to increase diabetes clients' compliance in controlling their disease. Purpose: The purpose of this activity is to provide knowledge and understanding to health cadres in providing education to the community regarding the importance of self-care management, especially in diabetes mellitus. Method: This activity is in the form of Diabetes Self Management Education (DSME) training for health cadres in Bumiayu village which will be held on Friday 25 August 2023 at 09.00 WITA. This activity was attended by 15 health cadres. Results: Based on the implementation of counseling about diabetes self-care management which was attended by the Bumiayu village health cadres, the results achieved can be described. Increasing the cadres' knowledge about self-care management, the cadres are able to educate about the importance of carrying out diabetes self-care management and the cadres are able to provide care or practice directly with the community about Diabetes self-care management. Conclusion: The implementation of training activities went well and smoothly. This activity received good input from health cadres with the result that the cadres' knowledge increased after being given the material. This community service activity can be carried out periodically to reduce the incidence of DM.